Learn Descriptive Cataloging - Second North American Edition - Mortimer, Mary (Total Recall Publications Inc, 2012)
This guide is equally suitable for college students studying library science, and library technicians and others who want to know more about cataloging, with a specific goal or as part of their professional development.